Cochlear implants - Bennington, Susan (Operating Room Nurses Association of Canada Journal, 1987)
The cochlear implant is an exciting new development that will ultimately help many profoundly deaf people. For a bilaterally deaf person with an intact auditory nerve who is unable to benefit from a conventional hearing aid, this information is very exciting.